Exploring relationships between size and function of trunk muscles, injuries and concussion in a professional rugby league team - Hides, J. A.; Leung, F.; Smith, M. M. F.; Anning, L.; Blanch, P.; Mendis, M. D. (Journal of Science in Sport and Exercise, 2025)
Purpose Examine for injury risk factors and establish clinical cut-off values related to size and function of trunk muscles.